Trace minerals in blood of young calves during exposure to lead - PATRA, R C; SWARUP, D; DWIVEDI, S K; SAHOO, A (The Indian Journal of Animal Sciences, 2014)
Crossbred calves (15), aged one month, Were given 7.5 mg oHead acetate/ kg body weight by oral route daily for.28 days to study the sequential effects of lead-exposure on trace minerals inblood. Control calves (5) were given no treatment Sequential alterations in the trace mineral profile in blood and biochemical parameters in serum were monitored at weekly interval during exposure to lead. Serial blllod sampling was carried out before exposure, to lead (day 0) and thereafter at weekly intetyal for 4 weeks. Haematobiochemical changes included decreased haemoglobin (Hp) and increased serum urea nitrogen. Increase in blood lead concentration in lead-exposed calves was associated with a decrease in blood copper and an increase in cobalt concentration. Blood zinc concentrationinthe lead-exposed ariimals on day iand therafter, was significantly higher than that of day 0 value. However, theS!i changes were not sufficient enough to become statistically different from respective control values. Similarly, significant changes in serum protein and glohulm levels wete tecorded on day 21 and 28, compared to respective control values. It is condudedthat micronutrIent profile and Hb level In the blood are altered by exposure to lead even in absence of overt clinical signs.